“The Past Dictates the Future”: Epistemic Ambivalence and the Compromised Ethics of Complicity in Twin Peaks: The Return and Fire Walk with Me - Joshua Jones (New York City College of Technology, 2020)
In this paper I explore questions of epistemology and complicity in Twin Peaks: The Return with reference to the original series and to Twin Peaks: Fire Walk with Me. I characterize these works as auto-exegetical texts (texts that critically read themselves), and I introduce the notion of epistemic ambivalence to describe how they proffer the possibility of teleological resolution while deliberately failing to provide enough information to realize that possibility. I examine how epistemic ambivalence is frequently deployed around questions of complicity with and culpability for evil, with the effect that the desire for certain knowledge and meaning is problematized by its connection to a masculinized desire for mastery. I argue that epistemic ambivalence is not just an important theme but is an integral characteristic of The Return’s ambivalently complicit story of violence and objectification. I reach two main conclusions: first, that the foregrounding of Laura’s pain in both Fire Walk with Me and The Return demands that audiences address and reflect upon our own complicity with the violence inflicted upon her; and second, that while there may be value in remaining attached to the desire for certain knowledge and to the dualistic conceptions of good and evil deployed ambiguously throughout Twin Peaks, there is perhaps more ethical and critical value to be found in exploring how these works engage the ambivalence such attachment engenders.